Análise ampla do genoma para detecção de erros de montagem no genoma de referência bovino e para detecção de locos relacionados a características de produção e reprodução da raça GIR - Utsunomiya, Adam Taiti Harth [UNESP] (2015)
The genetic basis of physiological processes underlying milk production traits are not completely understood, and few causal genes and markers associated with these traits have been reported to date. The emergence of the genomics era, efforts for the discovery of single nucleotide polymorphisms (SNPs) are numerous. These markers allow for establishing relationships between differences in economically important traits and specific genomic coordinates. These relationships are confirmed in genome-wide association studies (GWAS), which provide knowledge about genes and chromosomal segments affecting traits of interest that can be further explored in systems biology. Inferences about genomic localtions that are potentially implicated in phenotypic differences rely on a reference genome assembly where genes are annotated. However, genome assembly is a complex task that is prone to errors, and cases of wrong positioning of nucleotide sequences are not rare. Therefore, this thesis aimed at assessing candidate misassembled regions in the reference bovine genome assembly and performing a GWAS for milk traits in Gir cattle (Bos indicus), including milk, protein and fat yield, percentage of protein and fat, and age at first calving, targeting the identication of genomic regions that are potentially related to important aspects of fertility and milk production